Right Atrial Thrombus Associated with Central Venous Catheter after Surgical Repair of Co-arctation of Aorta - Bajracharya, Smriti Mahaju; Sapkota, Sandeep (Nepalese Heart Journal, 2021)
Central venous catheterization (CVC) is a routine and essential procedure performed in patients undergoing cardiac surgery. However, its use is not without complications ranging from mechanical to infectious to thrombotic in nature. Catheter-related right atrial thrombosis (CRAT) is usually underreported as it is commonly small in size and asymptomatic. Nevertheless, CRAT might lead to a potentially severe and life threatening complication in both adult and young patients. Up to 30% of patients with CVCs are estimated to be affected by CRAT. Anticoagulation and subsequently catheter removal were recommended as a first-line therapy and have suggested that no intervention may be associated with a high mortality rate. Here, we report a case of a 3-months-old male child who underwent coarctation of aorta repair and was diagnosed with right atrial thrombosis associated with CVC in postoperative period and anticoagulated with unfractionated heparin. The thrombus was followed up closely and when there was no further decrease in the size of the mass around 9 days after the diagnosis, the CVC was removed. The heparin was continued even after removal of CVC for further 7 days and patient was eventually discharged from the hospital.